Reinventing Government Pelayanan Mobil Siaga Desa - Diyah Norisa Retno; Muhammad Miftahul Huda; Junadi Junadi (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The state must provide high-quality public services to its citizens. Regular innovation in service delivery is important to ensure satisfaction among the recipients. The concept of reinventing government, which is a principle of New Public Management (NPM), is used as a reference for the bureaucracy to provide modern and reliable public services. Health services are crucial, especially in terms of transportation. Standby cars are an innovative example of transportation services provided by the government to facilitate public facilities and infrastructure. This study was conducted to examine the use of reinventing government principles in village standby car services. The research used descriptive methods, including observation, interviews, and documentation. The Social Service and the person in charge of managing the village alert car provided the data source. The findings revealed that there are still indicators not being met if the standby car service system refers to the principle of reinventing government, specifically the competitive government indicators. In conclusion, village standby car services have a significant impact on the community, especially those living in remote areas.